Exploratory Study on Bending Strength of Concrete with Nylon String Fibre - Samsuri, Nur Syakinah; David Yeoh (Recent Trends in Civil Engineering and Built Environment, 2026)
Nylon fiber reinforced concrete has taken on a new role in building industry. Among all other elements involved for transmitting stress between matrix and fibers, aspect ratio has asignificant impact on the mechanical characteristics of the concrete composite. This Abstract is compulsory. The study explores the use of natural nylon string fiber in concrete to enhance its performance, comparing its compressive and bending strength with standard concrete (grade 25) and concrete with nylon fiber at 1%, 2%, and 3% volume. After that, a total of 38 specimens (prisms and cubes) were left cure for a total 28 days in order to ascertein the concrete’s mean strength. As a result, the compressive strength enchanced 30.81 MPa with 2% of nylon fiber, the same as bending strength improved by 4.14 MPa after 28 days curing. Aside from that, the aim of this study is to produce nylon-fiber-reinforced concrete by adding 50 mm long and 0.16 mm diameter nylon fibers into concrete. In addition, increasing the percentage of nylon fibre in concrete could reduced its density.